The cyclic Douglas–Rachford algorithm with r-sets-Douglas–Rachford operators. (4th July 2019) - Aragón Artacho, Francisco J.; Censor, Yair; Gibali, Aviv
ABSTRACT: The Douglas–Rachford (DR) algorithm is an iterative procedure that uses sequential reflections onto convex sets and which has become popular for convex feasibility problems. In this paper we propose a structural generalization that allows to use r -sets-DR operators in a cyclic fashion. We prove convergence and present numerical illustrations of the potential advantage of such operators with r >2 over the classical 2-sets-DR operators in a cyclic algorithm.